Sistem Pakar Diagnosa Kerusakan Playstation2 Berbasis Web Dengan Metode Forward Chaining - Ludfi Sanjaya; Belsana Butar Butar (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Playstation2 is the best console of all time and has a major influence on the development of video games. So from that playstation2 until now still in demand in the community in all the game lovers. Basically the problem of damage to playstation2 is the most common case found in playstation2 and private rental employers who have playstation2. This damage requires fast and correct handling, as it can be quite detrimental to playstation2 rental entrepreneurs. Current technological advances to facilitate the work of man, because nowadays we can create an artificial intelligence that one of them called expert systems. For the development of expert systems requires hardware (hardware) such as a monitor, a processor, a minimum of 214 GB hard drive, 320 GB of memory, mouse and keyboard. Perangkat (software) consists Adove CS8 Dreamweaver, MySQL, XAMPP, Browser such as Mozilla. This application was designed with a web and an attractive appearance that can be used online for consultation. The results of this research is the application of playstation2 damage diagnosis expert system based on the indication symptoms of playstation2 problems. Keyword: Expert System, Forward Chaining, Playstation2 Diagnose, Web Based